Effectiveness of training in expressing positive emotions, reacting to change and greeting peers after childhood traumatic brain injury: a single-case experimental study - Rivas-García, Sandra; Paúl, Nuria; Catena, Andrés; Caracuel, Alfonso (Frontiers in Psychology, 2023)
Background Social cognitive deficits are common after traumatic brain injury (TBI). The participant in this single-case experimental design (SCED) was 7 years old when he sustained a severe TBI. After 2 years in rehabilitation, he continues to show deficits in social cognition. Objective To determine the effectiveness of three interventions, each aimed at improving a behavior altered by social cognition deficits. These behaviors were: (1) expression of positive emotions, (2) reacting to changes in plans, and (3) greeting classmates. Method An A-B-A’ design was used for each behavior. In addition, each behavior was targeted with a rehabilitation program applied over 10 sessions. Results For the first behavior, changes between phases B-A’ (NAP = 0.712) and A-A’ (NAP = 0.864) indicated improvements in the child’s ability to express positive emotions. In the second behavior, changes in the intensity of reactions between phases B and A’ (NAP = 0.815) and A vs. A’ (NAP = 0.834) indicated that the child adapted to changes in a plan and to unexpected situations in a more adaptive way. For the third behavior, changes in the number of greetings between phases A and B (NAP = 0.883) and A vs. A’ (NAP = 0.844) suggested that during the third phase of the study, the participant fully acquired the habit of greeting peers and increased his interactions with others. Conclusion While the participant showed improvements in all three targeted behaviors, due to the complexity of the third behavior, it is recommended that in future research, the intervention targeting social interactions should be applied over a longer timeframe to ensure that improvements are more stable in the long term.